DIGITAL INCLUSION AND GOVERNANCE EQUITY IN THE AGE OF TECHNOLOGICAL TRANSFORMATION - Desi Rahma Aryanti; Hilman Sutanto; Iman Ahmad Gymnastiar; Hendun Abd Rahman Shah (Alqaprint Jatinangor, 2025)
This study explores the intricate relationship between digital inclusion and governance equity amid rapid technological transformation. Through a comprehensive literature review, it synthesizes theoretical and empirical insights from recent scholarly works across global contexts. The analysis highlights how digital inclusion serves as both an enabler and a challenge to achieving equitable governance structures. Emerging technologies such as artificial intelligence, big data, and blockchain reshape institutional capacities and social participation mechanisms. However, disparities in digital literacy, access, and infrastructure continue to widen governance inequalities. The study identifies key policy frameworks promoting inclusive digital governance and evaluates their effectiveness in reducing social and economic disparities. It further discusses the ethical and regulatory implications of digital transformation in public administration. The review concludes that governance equity in the digital era demands multidimensional strategies integrating technology, policy, and social justice. These findings contribute to the broader discourse on sustainable digital governance and inclusive policymaking.